Sex chromosome and gonadal hormone contributions to binge-like and aversion-resistant ethanol drinking behaviors in Four Core Genotypes mice - Sneddon, Elizabeth A.; Masters, Brianna M.; Ream, Kiara D.; Fennell, Kaila A.; DeMedio, Jenelle N.; Cash, Miranda M.; Hollingsworth, Brynn P.; Pandrangi, Sai; Thach, Chloe M.; Shi, Haifei; Radke, Anna K. (Frontiers in Psychiatry, 2023)
Introduction While substantial research has focused on the contribution of sex hormones to driving elevated levels of alcohol drinking in female rodents, fewer studies have investigated how genetic influences may underlie sex differences in this behavior. Methods We used the Four Core Genotypes (FCG) mouse model to explore the contribution of sex chromosome complement (XX/XY) and gonad type [ovaries (Sry–)/testes (Sry+)] to ethanol (EtOH) consumption and quinine-resistant drinking across two voluntary self-administration tasks: limited access consumption in the home cage and an operant response task. Results For limited access drinking in the dark, XY/Sry + (vs. XX/Sry +) mice consumed more 15% EtOH across sessions while preference for 15% EtOH vs. water was higher in XY vs. XX mice regardless of gonad type. XY chromosomes promoted quinine-resistant drinking in mice with ovaries (Sry–) and the estrous cycle did not affect the results. In the operant response task, responding for EtOH was concentration dependent in all genotypes except XX/Sry + mice, which maintained consistent response levels across all concentrations (5–20%) of EtOH. When increasing concentrations of quinine (100–500 μM) were added to the solution, FCG mice were insensitive to quinine-punished EtOH responding, regardless of sex chromosome complement. Sry + mice were further found to be insensitive to quinine when presented in water. Importantly, these effects were not influenced by sensitivity to EtOH’s sedative effect, as no differences were observed in the time to lose the righting reflex or the time to regain the righting reflex between genotypes. Additionally, no differences in EtOH concentration in the blood were observed between any of the genotypes once the righting reflex was regained. Discussion These results provide evidence that sex chromosome complement regulates EtOH consumption, preference, and aversion resistance and add to a growing body of literature suggesting that chromosomal sex may be an important contributor to alcohol drinking behaviors. Examination of sex-specific genetic differences may uncover promising new therapeutic targets for high-risk drinking.